The effect of combined exercises on the development of some physiological and physical indicators of the Eduard - Ghaleb Oudah, Ishraq (International Journal of Psychosocial Rehabilitation, 2020)
The effect of compound exercises in developing some physiological and physical indicators of young players in fencing with fencing. The study aimed to prepare combined exercises that fit the capabilities of the research sample and to identify their effect on developing some physiological and physical indicators of young players in fencing with fencing. The researcher used the one-group experimental method. Included in the research sample were (8) players representing the central Iraqi national youth team in the fencing weapon blinds, who were selected purposefully, and the researcher proceeded to conduct test data carrying power of arms and legs Wa for agility in addition to the tests of physiological indicators (pulse, high blood pressure, and the pressure of the low blood pressure). For fencing players , Then deliberately T. researcher of the preparation exercises vehicle (physical-mharri), whose implementation took eight weeks by ( 24 ) and a training unit. The researcher concluded that the combined exercises led to the development of physical variables in a significant degree of statistical significance and for the benefit of telemetry , and the researcher also recommended relying on complex exercises when developing curricula for training fencing with fencing, as well as applying them to the junior category, especially the Specialized Center for Sports Talent for Duelists, because of their positive effect in raising the level of physical fitness of young fencer players.